التّقويم التّربوي و تنمية مهارات التّفكير - مأمون, سعاد; عريف, هنية (جامعة الوادي - University of Eloued, 2021)
حظي موضوع التفكير باهتمام العديد من الباحثين والمربين، حتى أصبح من أكثر الموضوعات دراسة وبحثاً لنهوض بالمناهج التربوية الحديثة وذلك أن هدف العملية التعليمية لم يعد قاصراً على تزويد المتعلمين بالمعارف والحقائق فقط بل تعداه إلى الاهتمام بعمليات التفكير ومهاراته المختلفة التي يكتسبها الفرد من خلال الممارسات التربوية والمناهج المختلفة مما يساعده على التعامل مع الكم الهائل للمعارف والمعلومات التي يستقبلها بفاعلية وتمكن ولذلك فقد أصبح هناك اهتمام متزايد بتعليم التفكير والتدريب عليه لتمكين المتعلم من مواجهة التحديات الحديثة واكتساب القدرة على حل المشكلات. ولعل أهم وسيلة لذلك هي الأسئلة الصفية والتي تعتبر أحد أشكال التقويم التربوي والذي من خلالها يتفاعل التلاميذ مع ما يقدم لهم من معارف ومعلومات في العملية التعليمة. فما هو دور الأسئلة الصفية في تنمية مهارات التفكير؟ اAbstract: The topic of thinking has received the attention of many researchers and educators, so that it has become one of the most studied and research topics for the advancement of modern educational curricula, as the goal of the educational process is no longer limited to providing learners with knowledge and facts only, but rather to interest in thinking processes and various skills that an individual acquires through educational practices and curricula. Which helps him to deal with the vast amount of knowledge and information that he receives effectively and is able, and therefore there has become an increasing interest in teaching thinking and training on it to enable the learner to face modern challenges and gain the ability to solve problems Perhaps the most important means for this are classroom questions, which are considered a form of educational evaluation through which students interact What is the role of classroom questions in developing thinking skills?
الأسّئلة الصّفية لتلاميذ السّنة الثّالثة من التّعليم المتوسّط نموذجاً
مقال
Keywords: التفكير ; الأسئلة الصفية ; التعليم ; المهارات, التقويم,مستويات التفكير; Class questions; thinking skills; Calendar; Education; Levels of thinking